Nano-curcumin in the decrease of proteinuria in white rats (Rattus norvegicus) with preeclampsia - Subandi; Sahara, Aulia Ilma; Nurdiana (Universitas Airlangga, 2024)
HIGHLIGHTS The size of curcumin was modified to nano scale in order to enhance its bioavailability and facilitate its absorption in the body. As a herbal medicine, nano-curcumin has the ability to reduce proteinuria and serve as a preventive measure against preeclampsia. ABSTRACT Objective: Since preeclampsia is one of the most serious hypertensive disorders in pregnancy, as it occurs in 5-7% of all pregnancies, and causes around 70,000 maternal deaths and 500,000 fetal deaths worldwide each year, this study aimed to determine the effect of nano-curcumin on proteinuria in pregnant white rats (Rattus norvegicus) with preeclampsia. Materials and Methods: In this study, 24 white rats (Rattus norvegicus) were randomly selected and divided into six groups. Inclusion criteria included healthy rats aged 8 weeks or older, with normal blood pressure and weight, while exclusion criteria included sick, deceased, or prematurely birthing rats, and those with high blood pressure. Treatment, administered over six days from gestational days 13-18, involved L-NAME and nano-curcumin injections. Groups included K- (no treatment) and K+, P1, P2, P3, and P4 (treated with L-NAME and varying nano-curcumin doses). Blood pressure and proteinuria were evaluated on gestation days 12, 15, and 19 to confirm the preeclampsia model and assess nano-curcumin's effect on proteinuria. Urine collected over 24 hours in metabolic cages preceded the rats' termination. Data analysis utilized IBM SPSS version 23, including the Shapiro-Wilk test, parametric independent sample t-tests, One-Way ANOVA tests, and LSD post-hoc tests to identify group differences. Results: The results of this study showed that nano-curcumin had the effect of reducing proteinuria in white rats with preeclampsia. The significant results of the One-Way Anova test was p=0.001 (p <0.05) and the LSD post-hoc test revealed that the effective dose was 25 mg/ml. It was found that higher nano-curcumin dose had a higher average of proteinuria. Conclusion: Nano-curcumin can affect proteinuria in preeclampsia. The most effective dose is 25 mg/ml.